Vocational Rehabilitation Services and Labor Market Outcomes for Transition‐Age Youth with Disabilities in Maine. (15th December 2022) - Yin, Michelle; Siwach, Garima; Lin, Dajun
Abstract: Using administrative data from Maine to quantify the effect of vocational rehabilitation (VR) services on employment outcomes for transition‐age youth with disabilities, we exploited the variation in VR counselors' propensity to develop Individualized Plans for Employment (IPEs) for VR youth as an instrument for service receipt. We found that among the estimated 36 percent of VR clients on the margin of service receipt, having an IPE implemented increases quarterly employment rate by 15.4 percentage points and quarterly earnings by 1, 442 (2018 dollars). We found heterogeneous program effects with individuals 18 or younger benefiting significantly more than those older than age 18 at the time of VR application. We estimate the annual real rate of return to be 10.2 percent for two years after VR case closure.